Studies of the antitumor mechanism of action of dermaseptin B2, a multifunctional cationic antimicrobial peptide, reveal a partial implication of cell surface glycosaminoglycans - Dos Santos, Célia (2017)
Dermaseptin-B2 (DRS-B2) is a multifunctional cationic antimicrobial peptide (CAP) isolated from frog skin secretion. We previously reported that DRS-B2 possesses anticancer and antiangiogenic activities in vitro and in vivo. In the present study, we evaluated the antiproliferative activity of DRS-B2 on numerous tumor cell lines, its cell internalization and studies of its molecular partners as well as their influences on its structure. Confocal microscopy using ([Alexa594]-(Cys0)-DRS-B2) shows that in sensitive human tumor cells (PC3), DRS-B2 seems to accumulate rapidly at the cytoplasmic membranes and enters the cytoplasm and the nucleus, while in less sensitive tumor cells (U87MG), DRS-B2 is found packed in vesicles at the cell membrane. Furthermore FACS analysis shows that PC3 cells viability decreases after DRS-B2 treatment while U87 MG seems to be unaffected. However, "pull down" experiments performed with total protein pools from PC3 or U87MG cells and the comparison between the antiproliferative effect of DRS-B2 and its synthetic analog containing all Damino acids suggest the absence of a stereo-selective protein receptor. Pretreatment of PC3 cells with sodium chlorate, decreases the antiproliferative activity of DRS-B2. This activity is partially restored after addition of exogenous chondroitin sulfate C (CS-C). Moreover, we demonstrate that at nanomolar concentrations CS-C potentiates the antiproliferative effect of DRS-B2. These results highlight the partial implication of glycosaminoglycans in the mechanism of antiproliferative action of DRS-B2. Structural analysis of DRS-B2 by circular dichroism in the presence of increasing concentration of CS-C shows that DRS-B2 adopts anα-helical structure. Finally, structure-activity-relationship studies suggest a key role of the W residue in position 3 of the DRS-B2 sequence for its antiproliferative activity.